Factors Associated with Colorectal Cancer Screening Among Cambodians, Vietnamese, Koreans and Chinese Living in the United States - Ma, PhD, Grace X.; Wang, PhD, Min Qi; Toubbeh, PhD, Jamil; Tan, MD, MPH, Yin; Shive, Steven; Wu, MD, Dunli (North American Journal of Medicine and Science, 2012)
The purpose of this community-based participatory study was to identify factors associated with colorectal cancer (CRC) screening compliance and non-compliance among Cambodians, Vietnamese, Koreans and Chinese men and women 50 years and older living in the United States. A cross-sectional design was used in the study. The completed sample included 815 Asian Americans which included Cambodians (N=215), Vietnamese (N=195), Koreans (N=94) and Chinese (N=311). A 95-item questionnaire was developed and pilot tested for content validity and reliability. An in-person data collection approach was utilized and participants were given choice in responding in English or their native language. Of the 815 participants, 79.1% (N=645) reported never-screened, 7.9% (N=64), non-compliance, and 13.0% (N=106) compliance. Education was significantly associated with never-screened for CRC for Vietnamese and Chinese; employment status for Cambodians and Koreans; lack of health insurance for Cambodians, Korean and Chinese; English fluency and years lived in the U.S. for Vietnamese, Koreans, and Chinese. Less acculturated Asian Americans were more likely to be never screened, but differentially across ethnic subgroups. Barriers to screening included lack of knowledge, language, transportation, and time. Increased culturally-targeted public awareness and education programs are needed to improve CRC screening and compliance among high risk Asian American ethnic subgroups.